Aesthetics in Nursing Practice as Experienced by Nurses in the Philippines: A Phenomenological Study - Kongsuwan, Waraporn; Betriana, Feni; Galvez, Barbara (Fakultas Ilmu-ilmu Kesehatan, 2025)
Nursing aesthetics, acknowledged as a fundamental pattern of knowing, emphasizes the integration of aesthetic dimensions into nursing practice; yet the lived experiences of Filipino nurses in this domain remain under‐investigated. Employing a phenomenological design, this study explored how 15 purposively selected nurses in Negros Oriental Province perceive and enact aesthetic care. Data were elicited through participant-generated drawings followed by semi structured interviews and analyzed using Kongsuwan’s framework for interpreting artistic works and texts. Rigor was maintained via Lincoln and Guba’s trustworthiness criteria—triangulation, member checking, thick description, and an audit trail. Four themes emerged: honoring persons as a whole, seeing things from the perspectives of others, intrinsic satisfaction from aesthetic care, and innovative, pleasant nursing interventions. Participants construed aesthetic nursing as a collaborative process that co creates meaningful patient experiences through therapeutic communication, needs assessment, and empathic engagement. These findings can inform healthcare organizations in developing policies and practices that foster aesthetic nursing. Future research should examine the longitudinal impact of aesthetic practice on patient outcomes, its relationship to nurse retention, and its adaptability across diverse clinical and cultural settings.